Phenotypic Consequences In vivo and In vitro of Rearranging the P Gene of RABV HEP-Flury - Mei, Mingzhu; Long, Teng; Zhang, Qiong; Zhao, Jing; Tian, Qin; Peng, Jiaojiao; Luo, Jun; Wang, Yifei; Lin, Yingyi; Guo, Xiaofeng (Frontiers in Microbiology, 2017)
Phosphoprotein (P) of the Rabies virus (RABV) is critically required for viral replication and pathogenicity. Here we manipulated infectious cDNA clones of the RABV HEP-Flury to translocate the P gene from its wild-type position 2 to 1, 3 or 4 in gene order, using an approach which left the viral nucleotide sequence unaltered. The recovered viruses were evaluated for the levels of gene expression, growth kinetics in cell culture, lethality in suckling mice and protection of mice. The results showed that viral replication was affected by the absolute value of N protein which was regulated by P protein. Viral lethality in suckling mice was consistent with the ratio of P mRNA in one complete transcription. The protection of mice induced by viruses was related to the antibody titer 5 weeks post-infection which might be regulated by G protein. However, the ability to induce cell apoptosis and viral spread were not only related to the viral replication but also to the ratio of related gene which affected by the gene position. These findings might not only improve the understanding of phenotype of RABV and P gene rearrangement, but also help rabies vaccine candidate construction.